2009
DOI: 10.1016/j.mito.2009.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Significant modulation of mitochondrial electron transport system by nicotine in various rat brain regions

Abstract: The mitochondrion is the organelle responsible for generation of most usable energy in a cell. It also plays an important role in a series of physiological processes such as apoptosis and proliferation. Although previous studies have demonstrated that nicotine modulates the morphology and function of mitochondria, the mechanism(s) underlying these effects is largely unknown. In this study, using a microarray consisting of 4,793 clones derived from a mouse dopamine cDNA library, we profiled the gene expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 81 publications
0
20
1
1
Order By: Relevance
“…The impact of cocaine exposure on mitochondrial functions reflects changes in expression of nuclear chromosomal genes, but it is unknown whether these changes resulted from direct toxic effects on mitochondrial inner membrane components or more indirect effects of mitochondrial toxicity, or on neural networks. Interestingly, changes in expression of genes related to mitochondrial functions were also observed in nicotine-exposed rats (23). However, we did not observe similar changes after alcohol exposure.…”
Section: Discussioncontrasting
confidence: 62%
“…The impact of cocaine exposure on mitochondrial functions reflects changes in expression of nuclear chromosomal genes, but it is unknown whether these changes resulted from direct toxic effects on mitochondrial inner membrane components or more indirect effects of mitochondrial toxicity, or on neural networks. Interestingly, changes in expression of genes related to mitochondrial functions were also observed in nicotine-exposed rats (23). However, we did not observe similar changes after alcohol exposure.…”
Section: Discussioncontrasting
confidence: 62%
“…These findings were also highly consistent with previous brain imaging studies that have revealed negative effects of cocaine on brain glucose metabolism (London et al, 1990; Lyons, Friedman, Nader, & Porrino, 1996; Macey, Rice, Freedland, Whitlow, & Porrino, 2004; Thanos, Michaelides, Benveniste, Wang, & Volkow, 2008). Furthermore, alteration of certain genes encoding for mitochondrial components induced by cocaine (Lehrmann et al, 2003) and nicotine (Wang, Kim, Donovan, Becker, & Li, 2009) exposure had also been reported previously.…”
Section: Molecular Adaptations Accompanying Early Response and Lonmentioning
confidence: 60%
“…Additionally, these studies suggest that acute early-stage drug use is associated with expression changes in acute early response genes (Vaccarino, Hayward, Nestler, Duman, & Tallman, 1992). In comparison, chronic substance exposure has been associated with widespread changes in expression of genes related to several diverse and fundamental cellular functions, including ion transport, chromosome remodelling, stress and immune response, cell adhesion, cell cycle, apoptosis, protein and lipid metabolism, and mitochondrial functions (Liu, Chen, Lerner, Brackett, & Matsumoto, 2005; Schroeder et al, 2008; Vilar et al, 2006; J. Wang, Kim, Donovan, Becker, & Li, 2009; Zhao et al, 2006).…”
Section: Non-additive Genetic Mechanisms Involved In Sudmentioning
confidence: 99%